Major diseases of cole crops and their management - Tripathi, Aradhika; Parkash, Chander; Kumar, Sandeep (Indian Farming, 2026)
Cole crops, including cabbage, cauliflower, broccoli and knol-khol are crucial vegetables for nutrition and income security in wide range of climate like temperate, sub-tropical and tropical regions in India. The production of these crops is threatened by diseases such as black rot, sclerotinia rot, and damping-off, which significantly reduce its yield and quality. This article describes the occurrence,symptoms, and epidemiology of these diseases occurring on major cole crops growing regions of Himachal Pradesh. These diseases can be managed by using integrated disease management strategies which combines cultural practices, resistant cultivars, seed treatment, and use of biological control agents such as Trichoderma spp. and Pseudomonas fluorescens, along with need based judicious use of chemicals. Adoption of eco-friendly bio-agent based measures is vital to ensure sustainable production, minimise economic losses, and maintain soil and environmental health.